СОМАТИКАЛЫҚ БИРЛИКЛЕРДИҢ ФРАЗЕОЛОГИЗМЛЕРДЕ ТИРЕК СӨЗ СЫПАТЫНДА БЕРИЛИЎИ - Шынназарова, С. (ILIM hám JÁMIYET, 2023)
The article analyzes somatic phraseology in the phraseological system of the Karakalpak language, discusses the use of somatic units in Turkic written monuments, considers the role and significance of somatic dominants in the formation of phraseology and conducts linguistic and cultural analysis.